Essential Oil Analysis and Antimicrobial Activities of Anthemis marschalliana ssp. pectinata and Anthemis cretica ssp. argaea from Turkey. - GULEC ALBAY, CANAN; ALBAY, MESUT; YAYLI, NURAN; YILDIRIM, NURI; COSKUNCELEBI, KAMIL; YAYLI, NURETTIN (Asian Journal of Chemistry, 2010)
The present work describes chemical composition and antimicrobial activity of the essential oils of Anthemis marschalliana Wild ssp. pectinata (Boiss) Grierson and Anthemis cretica L ssp. argaea (Boiss & Bal) Grierson. The essential oils were obtained from all the parts of the plant by hydrodistillation and analyzed by GC-FID and GC-MS. Forty two and forty four components representing 88.6 and 89.6 % of the total oils were characterized and the main components of these species were found to be spathulenol (21.7 %), humulene epoxide II (5.9 %), β-pinene (4.8 %) and α-bisabolol (4.6 %) from A. marschalliana ssp. pectinata and β-pinene (14.6 %), α-pinene (14.3 %), borneol (10.6 %) and β-acorenol (6.5 %) from A. cretica ssp. argae, respectively. The antimicrobial activities of the isolated essential oils of the plants were also investigated and they showed moderate antibacterial activity against Yersinia pseudotuberculosis and Bacillus cereus.